THE IMPACT OF GENTLE HUMAN TOUCH IN INCREASING BABY WEIGHT, BODY TEMPERATURE AND PULSE STABILITY ON PRETERM BABY - Yennita Maharani; Ari Suwondo; Triana Sri Hardjanti; Suharyo Hadisaputro; Dyah Fatmasari; Imam Djamaluddin Mashoedi (Belitung Raya Foundation, Indonesia, 2017)
Background: Touch is crucial for optimal growth and development of preterm babies. Gentle human touch is considered as a complementary treatment to spur their growth and development. Objective: To determine the effect of gentle human touch on weight gain, body temperature and pulse rate stability in preterm babies. Methods: This was a Randomized Controlled Trial (RCT) with pretest-posttest with control group. Thirty-nine respondents were selected by consecutive sampling, assigned into two treatment groups and one control group. Data were analyzed using MANOVA . Results: The results showed that there was statistically significant difference in body weight (p = 0.047), body temperature (p = 0.021), and pulse rate stability (p = 0.001) in preterm babies. Conclusion: Gentle human touch therapy twice a day is more effective in improving body weight, body temperature, and pulse rate stability in premature babies. It is recommended that gentle human touch be applied as an operational standard for premature baby care.